Comminution in the Minerals Industry - Tavares, Luís Marcelo M. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Size reduction processes represent a significant part of the capital as well as the operating cost in ore processing. Advancing the understanding of and improving such processes is worthwhile since any measurable enhancement may lead to benefits, which may materialize as reductions in energy consumption or wear or improved performance in downstream processes. This book contains contributions dealing with various aspects of comminution, including those intended to improve our current level of understanding and quantification of particle breakage and ore characterization techniques that are relevant to size reduction, as well as studies involving modeling and simulation techniques. The affiliations of the authors of the articles published in this book span 14 countries around the globe, which attests to the highly international nature of research in this field. The themes of the manuscripts also vary widely, from several that are more focused on experimental studies to those that deal, in greater detail, with the development and application of modeling and simulation techniques in comminution. Size reduction technologies more directly addressed in the manuscripts include jaw crushing, vertical shaft impact crushing, SAG milling, stirred milling, planetary milling, and vertical roller milling. Ores involved directly in the investigations include those of copper, lead-zinc, gold, and iron as well as coal, talc, and quartz.